Structural evolution analysis of PAN carbon fiber during preparation process using radial distribution function based on XRD - Lin, Xue; Wang, Cheng-Guo; Yu, Mei-Jie; Xu, Yong; Lin, Zhi-Tao; Zhang, Shan (Hang kong cai liao xue bao, 2013)
The structural evolution of PAN carbon fiber during preparation process was studied by using the X-ray Diffraction and radial distribution function. The results show that the graphite-like structure exists in the PAN fiber, which is the important basis of graphite microcrystalline structure. The nearest neighbor distance of PAN is 0.688 nm. The third neighboring distances of all carbon fibers are greater than that of graphite, indicating that planar six-member rings of graphene sheet are not formed between 500 degree C and 1250 degree C. The structure of fibers transforms from long-range order to long-range disorder, and then from short-range order to long-range order during the whole preparation process of carbon fiber.